Ostracods (Crustacea) from thermal waters, southern Altiplano, Argentina - Laprida, Cecilia (2006)
The ostracod fauna from la Terma hot spring (26°55′31'' S −68° 08′45.7''W, 4026m above sea level), Southern Altiplano, Argentina, is described and the pool itself characterized. The occurrence of ostracods in this type of environments is registered for the first time in Argentina. Six species were found, two of which are new to the fauna of Argentina: Penthesilenula incae (Delachaux) and Hemicypris panningi (Brehm). Two species were found for the first time in the Altiplano: H. panningi (Brehm) and Cypridopsis fuhrmanni (Mehes). Some comments concerning how and when these species could spread to populate the Dry Altiplano are discussed briefly taking into account paleoclimatic data. This paper provides the first record of recent ostracods from the Southern Altiplano, Argentina.